Sacubitril/valsartan decreases mortality in the rat model of the isoprenaline‐induced takotsubo‐like syndrome. (30th August 2021) - Ali, Anwar; Redfors, Björn; Alkhoury, Jessica; Oras, Jonatan; Henricsson, Marcus; Boren, Jan; Björnson, Elias; Espinosa, Aaron; Levin, Malin; Gan, Li‐Ming; Omerovic, Elmir
Abstract: Aims: Takotsubo syndrome (TTS) is an acute potentially reversible cardiac syndrome characterized by variable regional myocardial akinesia that cannot be attributed to a culprit coronary artery occlusion. TTS is an important differential diagnosis of acute heart failure where brain natriuretic peptides are elevated. Sacubitril/valsartan is a novel and effective pharmacological agent for the treatment of patients with heart failure. Our aim was to explore whether treatment with sacubitril/valsartan could prevent isoprenaline‐induced takotsubo‐like phenotype in rats. Methods and results: A total number of 186 Sprague–Dawley male rats were randomized to receive pretreatment with water (CONTROL, n = 62), valsartan (VAL, n = 62), or sacubitril/valsartan (SAC/VAL, n = 62) before receiving isoprenaline for induction of TTS. We recorded heart rate and blood pressure invasively. Cardiac morphology and function were evaluated by high‐resolution echocardiography 90 min after the administration of isoprenaline. We documented the survival rate at the time of echocardiography. Compared with the CONTROL group, the SAC/VAL group had less pronounced TTS‐like cardiac dysfunction and lower mortality rate, while the VAL group did not differ. Heart rate and blood pressure were not significantly different between the groups. Analysis of cardiac lipids was performed with mass spectrometry. The VAL and SAC/VAL groups had significantly higher levels of lysophosphatidylcholine (LPC), in particular LPC 18:1 and LPC 16:0. Conclusions: Pretreatment with sacubitril/valsartan but not with valsartan reduces mortality and attenuates isoprenaline‐induced apical akinesia in the TTS‐like model in rats. Sacubitril/valsartan could be a potential treatment option in patients with TTS in humans.